‘No one should be a hibakusha’: Young Japanese activist’s mission to share atomic bomb survivor stories (UN News, 2026)
A Japanese peace activist is hoping to promote global nuclear disarmament by keeping alive the stories of the atomic bomb survivors through the creation of a mobile museum.